1992
DOI: 10.1007/bf02591656
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and sequence analysis of the cDNA encoding human apolipoprotein H (β2-Glycoprotein I)*

Abstract: Apolipoprotein H, also known as beta-2-glycoprotein I, was purified from human serum, and antiserum produced to denatured apolipoprotein H detected a cDNA clone from a lambda gt11 library derived from human liver. This cDNA coded for the complete sequence of the mature protein. The cDNA insert, along with a polymerase chain reaction product which extended the 5' end of the message, were subcloned and both strands were sequenced. The apolipoprotein H precursor was found to code for 345 amino acids, 326 of which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…Although hepatocytes represent the main site of β 2 ‐GPI synthesis [9], the presence of β 2 ‐GPI mRNA has been demonstrated, by RT‐PCR, in fetal astrocytes, in cells from intestine and placenta [10,11]. More recently, we also detected β 2 ‐GPI mRNA in endothelial cells, lymphocytes, astrocytes and neurones [12].…”
Section: Introductionmentioning
confidence: 62%
“…Although hepatocytes represent the main site of β 2 ‐GPI synthesis [9], the presence of β 2 ‐GPI mRNA has been demonstrated, by RT‐PCR, in fetal astrocytes, in cells from intestine and placenta [10,11]. More recently, we also detected β 2 ‐GPI mRNA in endothelial cells, lymphocytes, astrocytes and neurones [12].…”
Section: Introductionmentioning
confidence: 62%
“…To shed light on this issue, we analyzed several normal rat tissues by different techniques. We began our studies on ApoH expression by performing Northern blot analysis on total RNAs, using a human apoH cDNA probe: this approach confirmed that the liver is the major site of biosynthesis for apoH (37).…”
Section: Discussionmentioning
confidence: 96%
“…The expression of apoH mRNA was initially detected by Northern blotting in human, rat and mouse liver and in two liver-derived cell lines, HepG2 and Hep3B (30,37,38). More recently apoH mRNA was found by RT-PCR on RNA extracted from other tissues (intestine, placenta, foetal astrocytes, lymphocytes) or cultured cells (transformed cell lines) such as choriocarcinoma, hepatoma (36), colon adenocarcinoma (35), neuroblastoma, umbilical vein endothelial cells (HUVEC, but not for Alvarado-de la Barrera, 39), astrocytoma, glioblastoma cells (40) and in monocytes (41).…”
Section: Introductionmentioning
confidence: 99%
“…ApoH, also known as β2-glycoprotein-I, is secreted from the liver [35] and exists in plasma as both free ApoH and bound to lipoprotein particles [36]. In the present study, ApoH levels were decreased in plasma from subjects with T2DM + high EIR compared with subjects with NGT.…”
Section: Figure 1 Plasma Protein Levels In Subjects With Ngt (White Bmentioning
confidence: 76%